2015
DOI: 10.21273/hortsci.50.6.857
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Weed Control Practices in Landscape Planting Beds: Part II—Chemical Weed Control Methods

Abstract: Use of preemergence and postemergence herbicides is the most effective and economical method of weed control in landscape planting beds. When used correctly, herbicides can provide satisfactory weed control, reduce labor costs, and cause little or no negative environmental impacts. Major factors in herbicide efficacy include choosing the correct herbicide for the weed species present, following proper calibration procedures, and applying herbicides at the correct timing. The objective of this review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Similarly, in studies with crop residues, satisfactory weed control has often been reported even in cases in which most of the herbicide was intercepted by surface residue (Crutchfield et al, 1986;Ghadiri et al, 1984). This is primarily because weed control usually increases as mulch depth increases, regardless of weed seed placement due to the inhibitory effects of mulch on weed germination and growth (Crutchfield et al, 1986;Chalker-Scott, 2007;Ghadiri et al, 1984;Marble et al, 2015aMarble et al, , 2015b. Although these data show that PS may adsorb less herbicide than PB or HW, more data are needed to evaluate long-term control with these combinations in a variety of environments.…”
Section: Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in studies with crop residues, satisfactory weed control has often been reported even in cases in which most of the herbicide was intercepted by surface residue (Crutchfield et al, 1986;Ghadiri et al, 1984). This is primarily because weed control usually increases as mulch depth increases, regardless of weed seed placement due to the inhibitory effects of mulch on weed germination and growth (Crutchfield et al, 1986;Chalker-Scott, 2007;Ghadiri et al, 1984;Marble et al, 2015aMarble et al, , 2015b. Although these data show that PS may adsorb less herbicide than PB or HW, more data are needed to evaluate long-term control with these combinations in a variety of environments.…”
Section: Ligninmentioning
confidence: 99%
“…ulching is one of the most widely adopted and effective methods of weed control in landscape planting beds (Chalker-Scott, 2007;Marble et al, 2015a). Although mulch is an effective weed management tool, preemergence herbicides may be used in combination with mulch to reduce labor costs associated with hand weeding, repeated application of postemergence herbicides, or both (Marble, 2015;Marble et al, 2015aMarble et al, , 2015bWilen and Elmore, 2007). In addition to weed control benefits, use of common mulch, such as PB or PS, has been shown to reduce runoff and leaching of preemergence herbicides, including pendimethalin, metolachlor, and isoxaben, by 35% to 74% in the landscape compared with application of these herbicides to bare soil (Knight et al, 2001).…”
mentioning
confidence: 99%
“…In the landscape industry, mulch is usually used in landscape beds for both aesthetic purposes and weed control and typically applied at 2-3 inches (Marble et al, 2015). Mulch is less commonly used in the nursery industry because of the increased cost and difficulty of application but may be used in longer term crops or for crops that are sensitive to PRE herbicide applications (Case et al, 2005).…”
Section: Formulationmentioning
confidence: 99%
“…Allelochemicals can also be used for weed management ( Table 1 ) as they act as natural herbicides. Advantages of these natural products over synthetic herbicides include: (1) Natural products exhibit structural diversity and possess complex structures that could be used as an alternative for herbicide discovery; (2) Readily decompose in nature; and (3) Contain a different mode of action compared with synthetic herbicides ( Duke et al, 1997 , 2000 ; Dayan et al, 1999 ), providing alternative action sites for herbicides needed to control weeds in areas where few synthetic products can be used ( Marble et al, 2015 ).…”
Section: Allelochemicals: Mechanism Of Control and Use As Natural Hermentioning
confidence: 99%